Social cognition, socioeconomic status and subjective well-being of Chinese migrant workers - Weichao Huang; Shipeng Su; Xiaoyu Sun (Scientific Reports, 2024)
Abstract Subjective well-being is based on the unity of internal and external needs, as well as material and non-material needs. However, existing research lacks consideration of the impact of both objective material conditions and subjective psychological cognition on the subjective well-being of migrant workers. Thus, based on data from the 2017 China General Social Survey, this paper applies ordered logit models and OLS models to investigate the impact of social cognition and socioeconomic status on the subjective well-being of migrant workers and their intergenerational differences. The results indicate that: (1) Social cognition has a significant impact, and the impact of fairness perception is more pronounced than depression perception and class change perception; (2) among socioeconomic status, personal income did not have a significant effect as education level, car ownership and house property ownership; (3) there are intergenerational differences. The emotional state of the older generation is the most critical factor influencing their subjective well-being. In contrast, the new generation is more concerned with their feelings about future expectations. The older generation is more concerned with their house property ownership, while the increase in income, education and car ownership can significantly increase the subjective well-being of the new generation. For this reason, we believe that the Chinese government should gradually change the existing urban and rural management system to create a fair and just social environment; make migrant workers receive the same protection as urban residents and improve the income distribution mechanism; pay attention to the social security of the older generation of migrant workers and the development opportunities of the new generation of migrant workers and their ability to integrate into the city to improve their subjective well-being.